EFISIENSI PENYISIHAN KADAR BOD PADA LIMBAH CAIR TAHU MENGGUNAKAN TANAMAN BAMBU AIR DENGAN SISTEM SUB SURFACE FLOW CONSTRUCTED WETLAND - Alfiani Nur Kholisah; Noven Pramitasari; Audiananti Meganandi Kartini (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2022)
The tofu industry in Indonesia is growing very rapidly due to the high public demand for tofu.. Most of the tofu industries in Indonesia are household-scale industries that are not equipped with waste treatment so that processing is needed, one of which is Phyto-treatment. In this research, tofu wastewater treatment is carried out using a water bamboo plant (Equisetum hyemale) through a sub-surface flow constructed wetland system. This study aims to eliminate the levels of organic pollutants in the tofu wastewater which can be seen from the levels of BOD (biological oxygen demand) and to determine the effect of the number of plants and the type of media on the BOD levels. The test was Phyto-treatment carried out for 20 days with a residence time of BOD testing on days 5, 10, 15, and 20. Based on the results of the study, the efficiency of removing BOD levels on day 20 in the X1Y1, X2Y1, X1Y2, and X2Y2 reactors was 40.93%, 79.10%, 26.53%, and 53.61%, respectively. The efficiency of removal of the highest BOD levels was found in the X2Y1 Reaktor. Meanwhile, based on the results of statistical tests using two-way ANOVA, it can be concluded that the number of plants and the type of media had a significant effect on the BOD levels